Delivery mode and intraventricular hemorrhage risk in very-low-birth-weight infants: Observational data of the German Neonatal Network. (May 2017) - Humberg, Alexander; Härtel, Christoph; Paul, Pia; Hanke, Kathrin; Bossung, Verena; Hartz, Annika; Fasel, Laura; Rausch, Tanja K.; Rody, Achim; Herting, Egbert; Göpel, Wolfgang
Abstract: Background: Very-low-birth-weight infants (VLBWI) are frequently delivered by cesarean section (CS). However, it is unclear at what gestational age the benefits of spontaneous delivery outweigh the perinatal risks, i.e. intraventricular hemorrhage (IVH) or death. Objectives: To assess the short-term outcome of VLBWI on IVH according to mode of delivery in a population-based cohort of the German Neonatal Network (GNN). Study design: A total cohort of 2203 singleton VLBWI with a birth weight <1500 g and gestational age between 22 0/7 and 36 6/7 weeks born and discharged between 1st of January 2009 and 31st of December 2015 was available for analysis. VLBWI were stratified into three categories according to mode of delivery: (1) planned cesarean section (n = 1381), (2) vaginal delivery (n = 632) and (3) emergency cesarean section (n = 190). Outcome was assessed in univariate and logistic regression analyses. Results: Prevalence of IVH was significantly higher in the vaginal delivery (VD) (26.6%) and emergency CS group (31.1%) as compared to planned CS (17.2%), respectively. In a logistic regression analysis including known risk factors for IVH, vaginal delivery (OR 1.725 [1.325–2.202], p ≤ 0.001) and emergency cesarean section (OR 1.916 [1.338–2.746], p ≤ 0.001) were independently associated with IVH risk. In the subgroup of infants >30 weeks of gestation prevalence for IVH was not significantly different in VD and planned CS (5.3% vs. 4.4%). Conclusions: Our observational data demonstrate that elective cesarean section is associated with a reduced risk of IVH in preterm infants <30 weeks gestational age when presenting with preterm labor.